Le Réemploi comme ressource première - Philippe Simay (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
Reuse is now one of the major practices of the circular economy. Its objective is to reduce the production of waste and limit the consumption of energy and raw materials by reusing materials from construction sites. But to what extent can reuse be a lever for ecological transition when it depends on its main criticism: the industrial production of waste? The article discusses the modalities of its emancipation and questions the role that it may play in developing an architecture that preserves inhabited environments.